Exploring the Effect of Blended Learning on Speaking Skill of the Eighth Grade Students at SMP Negeri 3 Dawan - Pande Gede Rio Caprian; I Putu Andre Suhardiana; I Gusti Ngurah Agung Wijaya Mahardika (Indo Publishing, 2026)
The purpose of this research to investigated the difference between the use of blended learning approach with discovery learning and blended learning with problem-based learning for students' speaking ability and to investigated students' perception of the use of blended learning on students' speaking skills in SMP Negeri 3 Dawan. The researcher used a quantitative method with a Quasi-Experimental design. The sample consisted of 26 students for the experimental group and 26 students for the control group: VIII A as the experimental group and VIII C as the control group. The research instrument used a speaking test and a questionnaire. In this research, the researcher collected the data from the pre-test, treatment, and Post-test. Data analysis used descriptive statistical analysis, test normality, test homogeneity, and an Independent T-test. Based on the result of this research, it can be concluded that first, there was a significant difference between the experimental group and the control group. This can be seen from the data showed t(50)= -5,442 p=<,001. Second, based on the results, there was a positive response to the use of blended learning in speaking learning. This can be seen from of the descriptive analysis in the questionnaire; the overall mean total score is 50.92. The total result was divided by 15, because there are 15 statements and the result was around 3.39. Based on these findings, it can be concluded that there was a significant difference between group blended learning and discovery learning and blended learning with problem-based learning.